2024
DOI: 10.3892/mmr.2024.13178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fullerenol C60 on lung and renal tissue in lower extremity ischemia‑reperfusion injury in sevoflurane‑treated rats

Ayşe Arpaci,
Zeynep Köksal,
Zeynep Yiğman
et al.

Abstract: The aim of the present study was to examine the effect of fullerenol C60 on lung and kidney tissue in sevoflurane-treated rats with lower extremity ischemia-reperfusion (IR) injury. A total of 30 Wistar albino rats weighing 225-275 g were used and were equally divided into five groups (n=6/group): i) Sham; ii) IR; iii) IR-fullerenol C60 (IR-FUL); iv) IR-sevoflurane; and v) IR-fullerenol C60-sevoflurane (IR-FUL-SEVO). Fullerenol C60 was administered intraperitoneally prior to lower extremity IR induction and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…We have previously shown, that water-soluble C 60 fullerenes prevent the restraint of stress-induced oxidative disorders in rat' brain and heart tissues [ 8 ] as well as an acute liver injury [ 9 ], diminish muscle fatigue in rats [ 10 ], markedly decrease the level of oxidative stress in diet-induced obesity rats [ 11 ] and, finally, realize therapeutic effects in the models of muscle injury and ischemia of the muscle soleus in rats [ 12 , 13 ]. Recenly the authors [ 14 , 15 ] demonstrated the protective effect of C 60 fullerene on liver tissue in liver ischemia reperfusion injury as well as on lung and renal tissue in lower extremity ischemia-reperfusion injury in rats, which opens up a prospect for its use in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown, that water-soluble C 60 fullerenes prevent the restraint of stress-induced oxidative disorders in rat' brain and heart tissues [ 8 ] as well as an acute liver injury [ 9 ], diminish muscle fatigue in rats [ 10 ], markedly decrease the level of oxidative stress in diet-induced obesity rats [ 11 ] and, finally, realize therapeutic effects in the models of muscle injury and ischemia of the muscle soleus in rats [ 12 , 13 ]. Recenly the authors [ 14 , 15 ] demonstrated the protective effect of C 60 fullerene on liver tissue in liver ischemia reperfusion injury as well as on lung and renal tissue in lower extremity ischemia-reperfusion injury in rats, which opens up a prospect for its use in biomedicine.…”
Section: Introductionmentioning
confidence: 99%